Effects of a parental program for preventing underage drinking - The NGO program strong and clear - Eriksson Charli; Özdemir Metin; Pettersson Camilla (BMC, 2011)
Abstract Background The present study is an evaluation of a 3-year parental program aiming to prevent underage drinking. The intervention was implemented by a non-governmental organization and targeted parents with children aged 13-16 years old and included recurrent activities during the entire period of secondary school. The program consisted of four different types of group and self-administered activities: parent meetings, family dialogues, friend meetings, and family meetings. Methods A quasi-experimental design was used following parents and children with questionnaires during the three years of secondary school. The analytic sample consisted of 509 dyads of parents and children. Measures of parental attitudes and behaviour concerning underage drinking and adolescents' lifetime alcohol consumption and drunkenness were used. Three socio-demographic factors were included: parental education, school, and gender of the child. A Latent Growth Modelling (LGM) approach was used to examine changes in parental behaviour regarding youth drinking and in young people's drinking behaviour. To test for the pre-post test differences in parental attitudes repeated measures ANOVA were used. Results The results showed that parents in the program maintained their restrictive attitude toward underage drinking to a higher degree than non-participating parents. Adolescents of participants were on average one year older than adolescents with non-participating parents when they made their alcohol debut. They were also less likely to have ever been drunk in school year 9. Conclusion The results of the study suggested that Strong and Clear contributed to maintaining parents' restrictive attitude toward underage drinking during secondary school, postponing alcohol debut among the adolescents, and significantly reducing their drunkenness.